Synthesis of Metal Catalysts from Industrial Waste Effluents and its Catalytic Application in Biginelli Reaction - B. Patel, Rashmi; H. Vekariya, Rajesh; D. Patel, Kinjal; D. Patel, Hitesh (Current Organocatalysis, 2016)
Background: Industries are using various metals containing salts, for various purposes. However, some amount of metal salts is leached, which creates environmental pollution. Removal of these pollutants is essential. Various groups are working to remove them by different techniques, but here we have applied simple techniques to extract and then these materials are used as a catalyst for the synthesis of organic compounds. Presently, as per our knowledge, this type of approach is adopted by us. Method: The ligand pyrazole-thiosemicarbazide was prepared by green chemistry method, which was well characterized by various analytical techniques. This ligand is used for the extraction of various salts of metal from the effluent. The metal salts are converted into metal complexes. The metal complexes from the waste are used for the preparation of important biologically active derivatives. Results: The ligand extracts the metals very fast. We have also studied the metal – ligand ratio and found that it is 1:1. These complexes are used as a catalyst for Biginalli reaction and in the presence of the catalysts the reaction is faster as compared to the absence of a catalyst. Conclusion: Based on a study we conclude that the ligand can work efficiently for the extraction of metal from the waste water. The formed complexes are the efficient catalysts for the preparation of dihydropyrimidines and its recycle and reuse.
Keywords: heterogeneous catalysis